A Thorough QT Study to Evaluate the Effects of a Supratherapeutic Dose of Sertraline on Cardiac Repolarization in Healthy Subjects. Issue 3 (27th November 2019) - Abbas, Richat; Riley, Steve; LaBadie, Robert R.; Bachinsky, Mary; Chappell, Phillip B.; Crownover, Penelope H.; Damle, Bharat
Abstract: The effect of steady‐state supratherapeutic sertraline (Zoloft) on QT interval was assessed in a single‐center, randomized, 3‐way crossover, double‐blind, placebo‐ and moxifloxacin‐controlled thorough QT study. Healthy adults received sertraline 400 mg/day, moxifloxacin 400 mg, and placebo, with a washout period (≥14 days) between treatments. A 12‐lead electrocardiogram was recorded in triplicate before dosing and at selected time points up to 72 hours after dosing. Analysis of covariance using a mixed‐effect model with sequence, period, treatment, time, and treatment‐by‐time interaction as fixed effects; subject within sequence as a random effect; and baseline QT corrected for heart rate using Fridericia formula (QTcF) as a covariate was conducted. A 90% confidence interval for the least squares (LS) mean difference in QTcF between active treatment and placebo was computed for each postdose time point. Exposure‐response was assessed using linear mixed‐effect modeling. Fifty‐four subjects were enrolled. Over 24 hours after dosing, the LS mean difference in QTcF for sertraline versus placebo ranged from 5.597 milliseconds to 9.651 milliseconds. The upper bound of the 90% confidence interval for the LS mean difference exceeded a predefined 10‐millisecond significance threshold at the 4‐hour postdose time point only (LS mean, 9.651 milliseconds [90% confidence interval, 7.635‐11.666]). In the exposure‐response analysis, QTcF values increased significantly with increasing sertraline concentration (slope = 0.036 milliseconds/ng/mL; P < .0001). Predicted change from baseline in QTcF at therapeutic maximum plasma sertraline concentration was 3.57 milliseconds. This thorough QTc study demonstrated a positive signal for QTc prolongation for sertraline at the steady‐state 400‐mg/day dose.